Sustainability Reporting and Financial Performance of Listed Consumer Goods Firm in Nigeria - Offiaeli, Grace Amarachukwu; Salawu , Rafiu Oyesola; Nwobu , Obiamaka (International Journal of Economics and Financial Issues, 2025)
This study investigated the effect of sustainability reporting on the financial performance of listed consumer goods companies in Nigeria. The study employed an ex-post facto research design. Data were collected from the public audited annual financial reports of ten consumer goods companies listed on the Nigerian Exchange Group over a ten-year period, from 2014 to 2023, In this study, sustainability reporting Global Reporting Initiative (GRI) is the independent variable, and return on assets (ROA) and net profit margin (NPM) are the dependent variables. Data were analysed using the Panel Ordinary Least Squares (POLS) approach. At a 5% significance level, the POLS regression results showed that sustainability reporting has a positive but statistically negligible effect on ROA. Again, NPM is positively impacted by sustainability reporting, but this effect is again statistically negligible at 5% significance. As a result, the study found that there is no statistically significant relationship between sustainability reporting and financial performance. The study concluded with the importance of improving the quality and disclosure of sustainability reporting. Based on these conclusions, the study recommends that rather than considering sustainability goals as stand-alone projects, they should be included in the main business strategy and operations of a company.